Comparative Analysis of Financial Performance in National Private Banks Period 2021-2023 Using Descriptive Statistics and AHP Method - Nasution, Mutiara Akbar; Ginting, Lukas Destria Putra; Fitri, Anisa (Economic: Journal Economic and Business, 2024)
This study aims to analyze the financial performance of five national private banks in Indonesia during the period 2021-2023 using descriptive statistical methods and the Analytic Hierarchy Process (AHP). The six main financial ratios analyzed in this study include Capital Adequacy Ratio (CAR), Operating Costs to Operating Income (BOPO), Non-Performing Loan (NPL), Net Interest Margin (NIM), Current Account Saving Account (CASA), and Loan to Deposit Ratio (LDR). The results of the analysis show that Bank Permata has the best performance with the highest AHP score (0.92), supported by strong capital and good operational efficiency. Bank Danamon and Bank Panin are in second and third place, with AHP scores of 0.88 and 0.87, respectively, driven by advantages in interest income and credit expansion. Bank CIMB Niaga and OCBC NISP are at the bottom, with AHP scores of 0.80 and 0.72, indicating obstacles in operational efficiency and credit risk management. This study concludes that capital stability, operational efficiency, and the balance between credit expansion and liquidity are the main factors in determining bank financial performance. These findings are expected to be a reference for investors, regulators, and bank managers in making strategic decisions related to banking financial management.